2018
DOI: 10.3390/ijms19041014
|View full text |Cite
|
Sign up to set email alerts
|

Probing Interactions between AuNPs/AgNPs and Giant Unilamellar Vesicles (GUVs) Using Hyperspectral Dark-field Microscopy

Abstract: Noble metallic nanoparticles (NPs) such as gold and silver nanoparticles (AuNPs and AgNPs) have been shown to exhibit anti-tumor effect in anti-angiogenesis, photothermal and radio therapeutics. On the other hand, cell membranes are critical locales for specific targeting of cancerous cells. Therefore, NP-membrane interactions need be studied at molecular level to help better understand the underlying physicochemical mechanisms for future applications in cancer nanotechnology. Herein, we report our study on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 41 publications
2
14
0
Order By: Relevance
“…One of the key events contributing to nanotoxicity is the interaction of ENMs with phospholipid membranes. For this reason, lipid membranes such as phospholipid vesicles are commonly exploited as a minimal model system for investigating the biological impact of ENMs [3][4][5][6][7] . It has been demonstrated that nanoparticles can be internalised within both cells or model membranes via non-specific interactions, in the absence of receptor-mediated uptake 4,6,8 .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…One of the key events contributing to nanotoxicity is the interaction of ENMs with phospholipid membranes. For this reason, lipid membranes such as phospholipid vesicles are commonly exploited as a minimal model system for investigating the biological impact of ENMs [3][4][5][6][7] . It has been demonstrated that nanoparticles can be internalised within both cells or model membranes via non-specific interactions, in the absence of receptor-mediated uptake 4,6,8 .…”
mentioning
confidence: 99%
“…Among the many possible ENMs, spherical gold nanoparticles (AuNPs) have emerged as promising candidates for biomedical diagnostic, therapeutic and photoelectrochemical applications [14][15][16] due to their facile surface chemistry, ease of synthesis and tuneable size. Depending on the specific AuNPs, membrane and dispersant properties, various interaction outcomes have been observed 5,6,12,[17][18][19] . For example, cationic 20 or hydrophobically 12 functionalised AuNPs (<5 nm) can successfully be internalised within the membrane bilayer.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…By using hyperspectral DFM, Lu et al probed the interactions of giant unilamellar vesicles (GUVs) between noble metal nanoparticles, such as gold and silver nanoparticles. These two kinds of nanoparticles displayed very different states on the GUVs, including the distribution position and the clustering states . Xiao et al investigated the diffusion behavior of viral capsid protein (VCP)-coated gold nanoparticles on living cell membranes.…”
Section: Accurate Analysis Applicationmentioning
confidence: 99%
“…Thus, they can be used as biomarkers in the early diagnosis of GI tumors 9. Synthetic NVs can be sub-divided into two groups: a conjugate mixture of nanoparticles (NPs) and vesicles such as the quantum dots (QDs) which are widely used in biomedical sensing and imaging applications;10 and human-engineered exosomes with diameters ranging from 50 to 200nm 11. The tumor-derived exosomes (TEXs), which carry proteins and RNAs (including microRNAs and messenger RNAs), are malignant vesicles that are prevalent in the serum of cancer patients.…”
Section: Introductionmentioning
confidence: 99%